Desarrollo sostenible en turismo: una propuesta para Machu Picchu - Regalado Pezúa, Otto (2006)
Raising awareness about the environmental risks faced by the Historical Sanctuary of Machu Picchu, providing tools for thinking that will contribute to addressing the Sanctuary’s problems, and finally, contributing to the debate by forwarding a proposal for the Sanctuary’s sustainable management are the purposes of this study. In the first section, statistics show Peru is basically a unipolar travel destination. The second section presents the complex problems identified at the Sanctuary. To conclude, the study presents a proposed solution, including setting up a structure to manage the Sanctuary’s strategic planning while abiding by the key principles of sustainable development.